Desentralisasi Fiskal dan Kinerja Tata Kelola Pemerintahan: Bukti Empiris dari Tingkat Kabupaten Kota di Indonesia: BPK, IPB University - Astriana, Septhia; Khoirunurrofik, Khoirunurrofik (Jurnal Ekonomi dan Kebijakan Pembangunan, 2024)
Decentralization policies are believed to be able to improve government governance, but research examining the relationship between decentralization and governance issues is still very limited. This study intends to examine the relationship between fiscal decentralization and governance performance as evaluated by SAKIP using panel data collected from 508 districts/cities in Indonesia between 2016 and 2021. Revenue indicators and expenditure indicators are used in the fiscal decentralization indicator. This study shows that fiscal decentralization, both in terms of revenue and expenditure, has a considerable favorable impact on governance performance using the Panel Ordered Probit Regression. The sub-sample study reveals that the impact of fiscal decentralization on governance performance varies depending on whether a jurisdiction is a district or a city, as well as whether it is located in the Java area or outside Java. Where district regional governments and regional governments outside of Java are more affected by fiscal decentralization.